Persicaria lapathifólia: Identification, Chemical Composition, Pharmacological Action, Prospects for Use in Medical Practice (Review) - A. A. Gudkova; A. S. Chistyakova; A. A. Kostyleva; A. S. Bolgov; A. I. Slivkin (Разработка и регистрация лекарственных средств)
Introduction. Knotweed (curlytop knotweed (curly pea)) – Persicaria lapathifólia Delarbre belongs to the buckwheat family Polygonaceae Juss., the genus Persicaria Mill. For a long time, the Persicaria lapathifólia did not exist as a separate species since 1989, the sorrel-leaved mountaineer has become an independent species. This is an annual herbaceous plant, repeating the main features of the genus Persicaria, and, as the main differences, having larger leaves, most often whitish-green flowers collected in dense inflorescences, peduncles and perianth of which have a large number of yellowish glands and a specific sweet smell.Text. Purpose of the work was to study the possible prospects for using the Persicaria lapathifólia as an official species. Currently, the plant is not used in medical practice and is considered an admixture in the collection of pharmacopoeial species of the genus Persicaria Mill. The plant is unpretentious to environmental conditions, is a weed, growing in absolutely all climatic zones, which indicates a rich procurement base. Despite the morphological similarity of the mountaineer sorrel with other species of the genus Persicaria, there is a sufficient amount of information in the literature regarding the identification of the object obtained as a result of a comprehensive morphological and anatomical assessment by microscopic methods (stereomicroscopy, luminescent microscopy, classical anatomy, petiolar anatomy), which allows a high the degree of reliability to eliminate errors in the procurement of raw materials and their further use. The chemical composition of Persicaria lapathifólia is represented by various classes of biologically active compounds, among which the most interesting are phenolic compounds (flavonoids), represented mainly by glycosides of quercetin and kaempferol. In addition, the plant is rich in vitamins, being a source of choline, organic and essential amino acids. Taking into account the peculiarities of the component composition of the mountaineer sorrel, the plant is considered as a source of phytopreparations with hemostatic, capillary-protective, antitumor, anti-inflammatory, antifungal effects.Conclusion. As a result of the generalization of the data available in the literature, the prospects of Persicaria lapathifólia to be introduced as a medicinal plant material and medicinal plant substance for the production of herbal medicines along with Persicaria maculosa and Persicaria hydropiper herb were revealed.